2009
DOI: 10.2166/wh.2009.114
|View full text |Cite
|
Sign up to set email alerts
|

Detection and phylogenetic analysis of hepatitis A virus and norovirus in marine recreational waters of Mexico

Abstract: An investigation was conducted to determine hepatitis A virus (HAV) and norovirus (NV) presence in marine recreational waters (MRWs) from two Mexican tourists beaches (Altata and Mazatlan), located at the northwestern state of Sinaloa, Mexico. Also, Binary Logistic Regression (BLR) analyses were conducted between physicochemical parameters (temperature, turbidity and salinity) and viral organisms (HAV and NV). A total of 32 MRWs samples were collected from April to July of 2006. Samples were processed accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…In comparison, Vieira et al [29] reported NV GII concentration was close to zero at all sampling points in the Negro River Basin in Brazil, whereas Pérez-Sautu et al [26] indicated a relationship of viral prevalence with the climate. As a result of the stability of the enteric viruses in water, most of the clinical cases have been reported in this cold season [24,30]. Our results differ from other studies that detected NV during the coldest months of the year; this could be due to contaminated water and represents a potential risk factor for regional diarrheic outbreaks.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In comparison, Vieira et al [29] reported NV GII concentration was close to zero at all sampling points in the Negro River Basin in Brazil, whereas Pérez-Sautu et al [26] indicated a relationship of viral prevalence with the climate. As a result of the stability of the enteric viruses in water, most of the clinical cases have been reported in this cold season [24,30]. Our results differ from other studies that detected NV during the coldest months of the year; this could be due to contaminated water and represents a potential risk factor for regional diarrheic outbreaks.…”
Section: Discussioncontrasting
confidence: 90%
“…In earlier studies, RV and NV detection in water samples has been well documented [23,24,25]. Félix et al [24] reported that NV was found in 15 beach water samples from Mexico, whereas Di Bartolo et al [25] reported that RV was found in five water samples from Italy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of NoVs was the highest in the Puzi River, followed by its tributaries, the Dongshi fishing port, and the coastal oyster breeding area. NoVs are often detected in water bodies, including marine environments, rivers, lakes, water parks, and swimming pools (Félix et al., 2010 ; Koh et al., 2011 ; Podewils et al., 2007 ; Sartorius et al., 2007 ; Wyn‐Jones et al., 2011 ). Additionally, NoVs are one of the most common viral agents associated with waterborne diseases worldwide and can potentially cause acute viral gastroenteritis in people of all age groups (Wyn‐Jones et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caliciviruses survive more than 14 days when placed directly into artificial seawater and held at 15°C [55], and feline caliciviruses, employed as a model for the measurement of human calicivirus stability in marine water, are themselves stable in marine water [56]. Several studies showed that 55% to 64.2% of coastal water samples were positive for adenovirus; 8.3% to 51.9% for hepatitis A virus (HAV); 12.5% to 19% for rotavirus; 7.5% for noroviruses and 3% for poliovirus in Brazil and Mexico [57][58][59]. These results highlight the problem of sewage discharge into coastal waters.…”
Section: Virusesmentioning
confidence: 99%